The role of the DEAD‐box RNA helicase DDX3 in mRNA metabolism. (18th April 2013) - Soto‐Rifo, Ricardo; Ohlmann, Théophile
Abstract: DDX3 belongs to the DEAD‐box proteins, a large family of ATP‐dependent RNA helicases that participate in all aspects of RNA metabolism. Human DDX3 is a component of several messenger ribonucleoproteins that are found in the spliceosome, the export and the translation initiation machineries but also in different cytoplasmic mRNA granules. DDX3 has been involved in several cellular processes such as cell cycle progression, apoptosis, cancer, innate immune response, and also as a host factor for viral replication. Interestingly, not all these functions require the catalytic activities of DDX3 and thus, the precise roles of this apparently multifaceted protein remain largely obscure. The aim of this review is to provide a rapid and critical overview of the structure and functions of DDX3 with a particular emphasis on its role during mRNA metabolism. WIREs RNA 2013, 4:369–385. doi: 10.1002/wrna.1165 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications